TAXES AND PROFITABILITY OF DEPOSIT MONEY BANKS IN SELECTED AFRICA COUNTRIES - Fasanmi, Ifeoluwa (Annals of Spiru Haret University. Economic Series, 2022)
This study examined the effect of taxes on profitability of Deposit Money Banks in selected Afrcan countries . Objectively, the study examined the effect of company income tax and education tax on profitability of DMBs in selected Afrcan countries in terms of return on equity and return on assets. Ex-post facto research design was adopted and the population covered all the 14 quoted Deposit Money Banks in Nigeria; out of which, 10 banks were purposively selected. Secondary data obtained from the audited annual financial statement of the selected banks for 10 years spanning from 2010-2019 was used. Panel regression of fixed and random effect estimation was to test the formulated hypotheses and this was carried out after descriptive statistics and Pearson correlation. It was discovered that corporate income tax exerts a positive but insignificant effect on profitability of deposit money banks in terms of return on equity and return on asset to the tune of 0.011(p=0.503 > 0.05) and 0.001(p=0.617 > 0.05) respectively. Education tax was found to have a positive and significant effect on return on equity to the tune of 0.006(p=0.047 < 0.05). However, it has a positive but insignificant effect on return on asset to the tune of 0.0005 (p=0.317 > 0.05). Based on the findings made, it was established that there was a statistically significant effect of taxes on the profitability of Deposit Money Banks in Nigeria. Thus, it was recommended that the tenets of the ability to pay tax on company income tax and education should be upheld by the relevant tax authorities in Nigeria. This might afford firms with financial crises and low profitability to pay commensurate taxes. Keywords: Company Income Tax, Education Tax, Return on Equity, Return on Assets